Factors influencing community pharmacists’ knowledge about women’s issues in epilepsy - Jairoun, Ammar Abdulrahman; Al-himyari, Sabba Saleh; Shahwan, Moyad; Hassan, Nageeb; AL-Tamimi, Saleh; Jairoun, Maimona; Zyoud, Saed H.; Alshehri, Abdullah S.; Alkhanani, Mustfa Faisal; Alhasani, Reem Hasaballah; Alharbi, Adnan S.; Alshehri, Fahad S.; et al. (Frontiers in Public Health, 2023)
Background Previous studies have highlighted instances where pharmacists lacked knowledge regarding women’s health issues related to epilepsy. Objectives To assess UAE community pharmacists’ knowledge, toward women’s issues in epilepsy. Methods a cross-sectional research method was employed. A team of seven pharmacy students in their final year visited a randomly selected sample of community pharmacies in the UAE and face-to-face interviews were conducted with the pharmacists using a structured questionnaire. The questionnaire includes two parts; Eight questions designed to elicit data about the demographics of the study participants and 12 questions eliciting insights into the participants’ knowledge of women’s issues in epilepsy. Results A total of 412 community pharmacist were recruited in the study. The overall level of knowledge about women’s issues in epilepsy was good and the average knowledge score was 81% with a 95% confidence interval (CI) [79.1, 82.7%]. The results of multivariate analysis showed higher knowledge scores in chain pharmacies (OR 1.37; 95% CI 1.12–1.67), Chief pharmacists (OR 1.44; 95% CI 1.01–2.06), Pharmacists in charge (OR 3.46; 95% CI 2.7–4.45), pharmacists with 1–5 Years of experience (OR 2.87; 95% CI 1.71–4.82), pharmacists with 6–10 Years (OR 2.63; 95% CI 1.58–4.38), pharmacists with >10 years (OR 3.13; 95% CI 2.03–4.83), graduation form regional universities (OR 1.37; 95% CI 1.12–1.67), graduation form international universities (OR 1.73; 95% CI 1.36–2.20) and receiving a training on epilepsy (OR 1.36; 95% CI 1.12–1.67). Conclusion While the findings reveal an overall promising level of knowledge among community pharmacists regarding the issues faced by women with epilepsy, pinpointing which clinical and demographic factors have the most significant impact on this knowledge would permit the implementation of tailored educational interventions. Workshops and modules targeting the issues faced by women with epilepsy would further raise the knowledge and competence among community pharmacists in this area, ensuring better pharmaceutical care for this population.